THE PECULIARITIES OF USE OF MODERN PROGRAMS IN THE DESIGN-PROJECTING OF JEWELRY - Рубанка, М. М.; Остапенко, Н. В.; Рубанка, А. І. (Art and Design, 2020)
The purpose of the article is to analyze the applicability of modern software for design-projecting of models of jewelry on the example of creation of a 3D model of a flat medallion; such process of creation includes the following steps: development of an algorithm; check for the errors; determination of the main characteristics. When conducting the researches, a set of general scientific approaches has been used, in particular: visual-analytical and system-informational approaches, modern methods of analysis of mechanical systems, as well as the method of classifications. The programs for three-dimensional modeling are listed; the peculiarities of their use and their functional possibilities are revealed. Based on the analysis of peculiarities of design-projecting of jewelry, the applicability of modern software is identified, in particular, the applicability of Rhinoceros 3D commercial software for three-dimensional NURBS-modeling. The development of engineering methods of designing of jewelry. The comparative analysis of programs for design-projecting of jewelry is performed. The proposed algorithm for creation of 3D model of a flat medallion using the Rhinoceros 3D software for three-dimensional NURBS-modeling is described. A standard algorithm for the creation of a 3D model of a flat medallion is developed. The recommendations regarding the use of Rhinoceros 3D software for three-dimensional NURBS-modeling in jewelry are made.